DESAIN PENGUJIAN PERATURAN PERUNDANG-UNDANGAN SECARA INTEGRATIF DI BAWAH MAHKAMAH KONSTITUSI - Sirajuddin Sirajuddin (Arena Hukum, 2018)
AbstractRegulations as products of a political  process and institution are  often contradicted with public aspirations and interests and potentially break the human right laws, therefore an open door to conduct a judicial review should be created.   The objective of this present study is to describe legal problematic matters arising  as the implication of  the adoption of a dualism testing of regulation in the constitutional system  of the Republic of Indonesia and to find an alternative model design of testing the regulations integratively under the authority of the Constitution Court of the Republic of Indonesia. The research results showed that  in the constitutional system of the Republic of Indonesia, injustice,  unuseefulnes, and uncertainty of law happened. To minimalize the condition, it is necessary to integrate the authority of the regulation under the hand of the Constitution Court through a further ammendment of the 1945 Constitution. However it is still necessary to have a demarcation line through the authority of the Constitution Court in interpreting the Constitution, since it may potentially result in the power abuse. It is indicated by some ultra petita decisions made by the Constitution Court that may potentially cause some new disorders in the political and juridical domains. Independence and accountability of juridical power should go hand in hand. Recruitment and supervision of Constitution Judges should involve the Judicial Commission.Abstrak Peraturan perundang-undangan sebagai produk dari proses sekaligus institusi politik seringkali berseberangan dengan aspirasi dan kepentingan publik, serta berpotensi menabrak norma HAM, sehingga harus terbuka ‘pintu’ untuk dilakukan judicial review. Penelitian dalam artikel ini bertujuan untuk  mendiskripsikan problematika hukum yang timbul sebagai implikasi dari dianutnya dualisme pengujian peraturan perundang-undangan dalam sistem ketatanegaraan Republik Indonesia dan; menemukan desain alternatif model pengujian peraturan perundang-undangan secara integratif di bawah Kewenangan Mahkamah Konstitusi Republik Indonesia. Hasil penelitian menunjukkan in ketatanegaraan Republik Indonesia terbukti menimbulkan ketidakadilan, ketidakmanfaatan, dan ketidakpastian hukum. Untuk meminimalisir kondisi tersebut, diperlukan pengintegrasian kewenangan pengujian peraturan perundang-undangan di bawah Mahkamah Konstitusi melalui perubahan lanjutan UUD 1945.  Namun demikian tetap diperlukan adanya garis demarkasi terhadap kewenangan MK dalam menafsirkan konstitusi, karena berpotensi menciptakan penyelewengan kekuasaan. Hal ini diindikasikan oleh beberapa putusan MK yang ultra petita berpotensi menimbulkan kekacauan baru dalam ranah politis dan yuridis. Independensi dan akuntabilitas kekuasaan kehakiman harus berjalan seiring. Rekruitmen dan pengawasan hakim konstitusi perlu melibatkan Komisi Yudisial.